Circulating MicroRNAs in Elderly Type 2 Diabetic Patients - Giuseppina Catanzaro; Zein Mersini Besharat; Martina Chiacchiarini; Luana Abballe; Claudia Sabato; Alessandra Vacca; Paola Borgiani; Francesco Dotta; Manfredi Tesauro; Agnese Po; Elisabetta Ferretti (International Journal of Endocrinology)
The circulating microRNAs (miRNAs) associated with type 2 diabetes (T2D) in elderly patients are still being defined. To identify novel miRNA biomarker candidates for monitoring responses to sitagliptin in such patients, we prospectively studied 40 T2D patients (age > 65) with HbA1c levels of 7.5–9.0% on metformin. After collection of baseline blood samples (t0), the dipeptidyl peptidase-IV (DPP-IV) inhibitor (DPP-IVi) sitagliptin was added to the metformin regimen, and patients were followed for 15 months. Patients with HbA1c < 7.5% or HbA1c reduction > 0.5% after 3 and 15 months of therapy were classified as “responders” (group R, n=34); all others were classified as “nonresponders” (group NR, n=6). Circulating miRNA profiling was performed on plasma collected in each group before and after 15 months of therapy (t0 and t15). Intra- and intergroup comparison of miRNA profiles pinpointed three miRNAs that correlated with responses to sitagliptin: miR-378, which is a candidate biomarker of resistance to this DPP-IVi, and miR-126-3p and miR-223, which are associated with positive responses to the drug. The translational implications are as immediate as evident, with the possibility to develop noninvasive diagnostic tools to predict drug response and development of chronic complications.